To find \(-24 \frac{4}{5} - 6 \frac{7}{10}\) using the additive inverse, we convert the subtraction into addition using the additive inverse of the second number.
-
First, let's convert the two mixed numbers into improper fractions:
-
For \(-24 \frac{4}{5}\):
- \(24 \times 5 + 4 = 120 + 4 = 124\), so \(-24 \frac{4}{5} = -\frac{124}{5}\).
-
For \(6 \frac{7}{10}\):
- \(6 \times 10 + 7 = 60 + 7 = 67\), so \(6 \frac{7}{10} = \frac{67}{10}\).
-
-
Now, we rewrite the subtraction using the additive inverse: \[ -24 \frac{4}{5} - 6 \frac{7}{10} = -\frac{124}{5} + \left(-\frac{67}{10}\right). \]
-
To add these fractions, we need a common denominator. The least common multiple of 5 and 10 is 10. We convert \(-\frac{124}{5}\) to a denominator of 10: \[ -\frac{124}{5} = -\frac{124 \times 2}{5 \times 2} = -\frac{248}{10}. \]
-
Now, our expression looks like this: \[ -\frac{248}{10} - \frac{67}{10} = -\frac{248 + 67}{10} = -\frac{315}{10}. \]
-
Simplifying \(-\frac{315}{10}\): \[ -\frac{315}{10} = -31 \frac{5}{10} = -31 \frac{1}{2}. \]
So the final result is \(-31 \frac{1}{2}\).
The correct response is: −31 1/2.